2012
DOI: 10.1029/2012gl053926
|View full text |Cite
|
Sign up to set email alerts
|

Satellite constraints of Nitrogen Oxide (NOX) emissions from India based on OMI observations and WRF-Chem simulations

Abstract: [1] In this work, we map and develop for the first time an independent satellite constrained NO x emission inventory for India for 2005 using an inverse technique and iterative procedure. We used OMI tropospheric NO 2 column retrievals over the Indian region, with tropospheric NO 2 columns simulated by the WRF-Chem model using the INTEX-B emission inventory. We determined the local relationship between modeled emissions and tropospheric columns and iteratively apply this relationship to OMI observations to der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 23 publications
3
84
0
Order By: Relevance
“…Some of the facts that support the in situ observations obtained from MOZAIC in Hyderabad are discussed here. One of the major factor that could lead to an increase in the near-surface level (0Á2 km) of CO and O 3 mixing ratios over the Hyderabad is the increase in anthropogenic emissions in the past decade (Beig and Brasseur, 2006;Ghude et al, 2013). Ghude et al (2013) reported the increase of NO x emissions by more than approximately 65 % in Hyderabad; however, the world's CO concentration has declined during the same period.…”
Section: Seasonal and Interannual Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the facts that support the in situ observations obtained from MOZAIC in Hyderabad are discussed here. One of the major factor that could lead to an increase in the near-surface level (0Á2 km) of CO and O 3 mixing ratios over the Hyderabad is the increase in anthropogenic emissions in the past decade (Beig and Brasseur, 2006;Ghude et al, 2013). Ghude et al (2013) reported the increase of NO x emissions by more than approximately 65 % in Hyderabad; however, the world's CO concentration has declined during the same period.…”
Section: Seasonal and Interannual Variabilitymentioning
confidence: 99%
“…One of the major factor that could lead to an increase in the near-surface level (0Á2 km) of CO and O 3 mixing ratios over the Hyderabad is the increase in anthropogenic emissions in the past decade (Beig and Brasseur, 2006;Ghude et al, 2013). Ghude et al (2013) reported the increase of NO x emissions by more than approximately 65 % in Hyderabad; however, the world's CO concentration has declined during the same period. It is also interesting to note the reported trends (Granier et al, 2011) from comparing several global and regional emission inventories.…”
Section: Seasonal and Interannual Variabilitymentioning
confidence: 99%
“…Satellite NO 2 data have been used as a proxy for (1) NO x emissions (van der A et al, 2017;Beirle et al, 2011;Boersma et al, 2015;Castellanos and Boersma, 2012;Curier et al, 2014;Ding et al, 2015;Duncan et al, 2014, de Foy et al, 2014Ghude et al, 2013;Jaeglé et al, 2004;Konovalov et al, 2006Konovalov et al, , 2010Lamsal et al, 2011;Liu et al, 2016;Lu et al, 2015;Lu and Streets, 2012;Martin et al, 2006;McLinden et al, 2016;Mijling and Van Der A, 2012;Richter et al, 2004Richter et al, , 2005Russell et al, 2012;Stavrakou et al, 2008;Streets et al, 2013;Vinken et al, 2014;Zhang et al, 2007;Zhou et al, 2012); (2) groundlevel NO 2 (Lamsal et al, 2008) and NO 2 deposition (Nowlan et al, 2014); and (3) emissions of co-emitted gases, including other pollutants, like particulate matter, and greenhouse gases, such as CO 2 (Berezin et al, 2013;Konovalov et al, 2016;Reuter et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 observations from satellite offer a globally consistent data set, albeit at coarse resolutions of 10 s to 100 s of kilometers, enabling a wide range of applications including many not feasible from in situ observations. Several studies have used satellite observations of NO 2 to evaluate chemical transport models (Martin et al, 2002;van Noije et al, 2006;Lamsal et al, 2008;Kim et al, 2009;Herron-Thorpe et al, 2010;Huijnen et al, 2010), examine spatial and temporal patterns of NO x emissions (Beirle et al, 2003;Richter et al, 2005;Kim et al, 2006;van der A et al, 2006;Zhang et al, 2007;Boersma et al, 2008a;Lu and Streets, 2012;Wang et al, 2012;Hilboll et al, 2013;Russell et al, 2010Russell et al, , 2012Duncan et al, 2013), examine NO x sources (Jaeglé et al, 2005;van der A et al, 2008;Bucsela et al, 2010;de Wildt et al, 2012;Lin, 2012;Ghude et al, 2010Ghude et al, , 2013aMebust et al, 2011;Mebust and Cohen, 2013), provide top-down constraints on surface NO x emissions Konovalov et al, 2006;Zhao and Wang, 2009;Lin et al, 2010;Lamsal et al, 2011;Ghude et al, 2013b;Vinken et al, 2014), infer NO x lifetimes (Schaub et al, 2007;Lamsal et al, 2010;Beirle et al, 2011), and estimate surface NO 2 concentrations …”
Section: Introductionmentioning
confidence: 99%